DIGITAL TRANSFORMATION OF CONTRACT LAW IN UKRAINE - Iryna Banasevych; Ruslana Heints; Ivan Kostiv; Nadiia Petechel (Diponegoro Law Review, 2025)
The rapid digitalization of society has fundamentally reshaped how contracts are concluded, executed, and disputed, particularly accelerating during the COVID-19 pandemic. While legal scholarship has addressed isolated aspects, such as the validity of smart contracts, electronic signatures, or digital property rights, there remains a significant gap in analyzing how digital tools collectively transform all stages of contractual relations. This study addresses that gap by systematically examining the legal challenges arising from digitalization, including party identification, verification of intent, probative value of electronic evidence, and liability for algorithmic decision-making. The novelty of this work lies in its integrated and comparative approach: combining doctrinal analysis of Ukrainian law, empirical case studies, and benchmarking against international standards such as the EU eIDAS Regulation and the UN Convention on Electronic Communications. The study contributes to legal science and practice by identifying inconsistencies in current regulation, evaluating the adaptability of Ukraine’s legal system to global digital standards, and proposing targeted reforms to strengthen contract law in the digital age. These findings are intended to support policymakers, practitioners, and academics in developing a more flexible, secure, and harmonized framework for digital contractual relations.